Design and implementation of learning platform for free space optical communications - Heng, Joel Yijun (2015)
Research bodies and institutes are pushing for more advancement in the field of photonics and optics locally. Thus, it is an opportunistic time for students to gain exposure to this field of engineering. This project presents and proposes a way to do this by designing and constructing a type of free space optical communication platform to EE2073. The learning platform and helpful lab manuals will form a learning package which will fit into the current EE2073 syllabus. Through this extra learning package fitted into EE2073, students will learn about photonics and optics in a fun, engaging and interesting way.